If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4 + -3n) = 3(n + 1) (4 * -2 + -3n * -2) = 3(n + 1) (-8 + 6n) = 3(n + 1) Reorder the terms: -8 + 6n = 3(1 + n) -8 + 6n = (1 * 3 + n * 3) -8 + 6n = (3 + 3n) Solving -8 + 6n = 3 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. -8 + 6n + -3n = 3 + 3n + -3n Combine like terms: 6n + -3n = 3n -8 + 3n = 3 + 3n + -3n Combine like terms: 3n + -3n = 0 -8 + 3n = 3 + 0 -8 + 3n = 3 Add '8' to each side of the equation. -8 + 8 + 3n = 3 + 8 Combine like terms: -8 + 8 = 0 0 + 3n = 3 + 8 3n = 3 + 8 Combine like terms: 3 + 8 = 11 3n = 11 Divide each side by '3'. n = 3.666666667 Simplifying n = 3.666666667
| 4(k-16)-1=11 | | N^2=3n+40 | | 16+14= | | 8-2(5x-3)+4x= | | 3y(y^2-4)= | | -14k-(-17k)-2k-(-3)=18 | | -6y+2x=-4 | | 2+(n+6)=10 | | -14r+19r-8r=18 | | 7n^2-2n=-3 | | 5a-12b-3b+10a+18a-13a+a= | | 19=2(v-9)-(-5) | | 6y-5y=11 | | 9=-3(v+5) | | 6=-k^2-7k | | -12-7x=9x-116+13 | | 19z-17z-z+3z=20 | | 7x+3-5x= | | (y+Z)(y+z)=2yz | | -2b-16b+17b+-2=2 | | 9+9s=10s | | -5c+9=-20 | | 3x^2+2y-y=-4 | | 3(4-4)=34 | | 8g+-7g=6 | | 14p-12p=20 | | 20x-10-45x-15=6x-18 | | 11a-8=16+5a | | 2x+16=5x+2 | | 5v^2=-11+12v | | 20=5y+30 | | -536+(-245)= |